Coupling analysis between resonating metamaterial slabs using scattering parameters. (September 2021) - Hasar, Ugur Cem; Kaya, Yunus; Izginli, Mucahit; Ozturk, Hamdullah; Ertugrul, Mehmet; Ramahi, Omar M.
Abstract: Metamaterial (MM) slabs in close proximity can couple with one another. This coupling can modify the electromagnetic response of the overall MM structure involving individual MM resonators. The signal flow graph technique along with the ABCD parameters are applied to quantitatively and qualitatively examine this coupling from simulated/measured scattering parameters of cascade connection of closely or largely separated MM slabs. S-parameter measurements of a MM slab constructed by split-ring-resonators were carried out at X-band (8.2-12.4 GHz) to validate our theoretical analysis. Highlights: Quantitative and qualitative coupling analysis between metameterial(MM) slabs is done. The signal flow graph technique along with the ABCD parameters are applied. Scattering (S-) parameters of the coupling network between MM slabs is extracted. Coupling network has non-zero reflection and non-unity transmission for coupled MMs.